2006
DOI: 10.5194/hess-10-65-2006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and measurement of two-layer-canopy interception losses in a subtropical evergreen forest of central-south China

Abstract: Abstract.The original Gash analytical model and the sparse Gash's model were combined to simulate rainfall interception losses from the top-and sub-canopy layers in Shaoshan evergreen forest located in central-south China in 2003. The total estimated interception loss from the two canopy layers was 334.1 mm with an overestimation of 39.8 mm or 13.5% of the total measured interception (294.3 mm). The simulated interception losses of the top-and sub-canopy suggested that the simulated interception losses in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 48 publications
4
16
0
3
Order By: Relevance
“…First, due to the decreasing coefficient of variation with increasing event size (Fig. 5a) (Brauman et al, 2010;Carlyle-Moses et al, 2004;Holwerda et al, 2006;Loustau et al, 1992;Price and Carlyle-Moses, 2003;Staelens et al, 2006;Vrugt et al, 2003;Zhang et al, 2006;Zimmermann et al, 2009), the sampling effort necessary to reach a pre-specified error limit of mean throughfall estimates decreases alike (Kimmins, 1973;Price and Carlyle-Moses, 2003;Rodrigo and Àvila, 2001;Zimmermann et al, 2010). The results of our study are in line with these findings (Figs.…”
Section: Implementing Throughfall Sampling Schemes: Influence Of the supporting
confidence: 82%
See 1 more Smart Citation
“…First, due to the decreasing coefficient of variation with increasing event size (Fig. 5a) (Brauman et al, 2010;Carlyle-Moses et al, 2004;Holwerda et al, 2006;Loustau et al, 1992;Price and Carlyle-Moses, 2003;Staelens et al, 2006;Vrugt et al, 2003;Zhang et al, 2006;Zimmermann et al, 2009), the sampling effort necessary to reach a pre-specified error limit of mean throughfall estimates decreases alike (Kimmins, 1973;Price and Carlyle-Moses, 2003;Rodrigo and Àvila, 2001;Zimmermann et al, 2010). The results of our study are in line with these findings (Figs.…”
Section: Implementing Throughfall Sampling Schemes: Influence Of the supporting
confidence: 82%
“…A sample size of 10 to 50 funnel-type collectors seems to be typical for many studies (Fig. 4, Supplementary material S1); only a few throughfall and interception studies had sampling schemes which involved a larger number of collectors (Gerrits et al, 2010;Manfroi et al, 2006;Price and Carlyle-Moses, 2003;Zhang et al, 2006). For trough-type collectors we tested sample sizes of 2, 5, 10, 20, and 50.…”
Section: Step 5: Simulation Of Throughfall Fieldsmentioning
confidence: 99%
“…Embora alguns pesquisadores tenham obtido sucesso com seu uso, na teoria o modelo superestima a perda por interceptação em florestas escassas. Por conta dessa deficiência, Gash et al (1995) e Valente et al (1997, respectivamente, revisaram o modelo original para aplicação nessas florestas (ZHANG et al, 2006). Apesar da grande importância que uma floresta exerce dentro do contexto do balanço hídrico local, ainda são poucos os estudos sobre a partição das chuvas por floresta de Mata Atlântica (ARCOVA, 2003).…”
Section: Introductionunclassified
“…Operating in a pine-oak stand in Mexico's Sierra Madre Oriental, Carlyle-Moses and Price (2007) found that the single storm versions of both Liu and Gash models underestimated empirical I c because predetermined S c and E c values were too small. Finally, there is growing evidence that E c inferred from throughfall is generally higher than E c derived from the Penman-Monteith equation (Zhang et al, 2006, and citations therein), which would lead to a general overestimation of I c , as in our study.…”
Section: The Liu Modelmentioning
confidence: 45%